Disruption of Slc4a10 augments neuronal excitability and modulates synaptic short-term plasticity - Sinning, Anne; Liebmann, Lutz; Hübner, Christian A. (Frontiers in Cellular Neuroscience, 2015)
Slc4a10 is a Na+-coupled Cl–HCO3- exchanger, which is expressed in principal and inhibitory neurons as well as in choroid plexus epithelial cells of the brain. Slc4a10 knockout mice have collapsed brain ventricles and display an increased seizure threshold, while heterozygous deletions in man have been associated with idiopathic epilepsy and other neurological symptoms. To further characterize the role of Slc4a10 for network excitability, we compared input-output relations as well as short and long term changes of evoked field potentials in Slc4a10 knockout and wildtype mice. While responses of CA1 pyramidal neurons to stimulation of Schaffer collaterals were increased in Slc4a10 knockout mice, evoked field potentials did not differ between genotypes in the stratum radiatum or the neocortical areas analyzed. Paired pulse facilitation was diminished in the hippocampus upon disruption of Slc4a10 and paired pulse depression was increased in the neocortex. Though short term plasticity is modulated via Slc4a10, long term potentiation appears independent of Slc4a10. Our data support that Slc4a10 dampens neuronal excitability and thus sheds light on the pathophysiology of SLC4A10 associated pathologies.